2020
DOI: 10.1021/acsnano.9b07307
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Aromatic Amino Acid Enantiomers into Supramolecular Materials of High Rigidity

Abstract: Most natural biomolecules may exist in either of two enantiomeric forms. Although in nature, amino acid biopolymers are characterized by l-type homochirality, incorporation of d-amino acids in the design of self-assembling peptide motifs has been shown to significantly alter enzyme stability, conformation, self-assembly behavior, cytotoxicity, and even therapeutic activity. However, while functional metabolite assemblies are ubiquitous throughout nature and play numerous important roles including physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
126
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 77 publications
(126 reference statements)
1
126
1
1
Order By: Relevance
“…Biomolecule self-assembling is highly implicated in various biologic events through a variety of non-covalent interactions, such as hydrophobic interaction, hydrogen bonds, electrostatic interaction, and metal coordination (Bera et al, 2020;Yu et al, 2020). The self-assembly structures are the basis of forming different complex biological structures (Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecule self-assembling is highly implicated in various biologic events through a variety of non-covalent interactions, such as hydrophobic interaction, hydrogen bonds, electrostatic interaction, and metal coordination (Bera et al, 2020;Yu et al, 2020). The self-assembly structures are the basis of forming different complex biological structures (Cao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[21] In particular, heterochiral peptide-based systems offer many advantages such as increased stiffness of the self-assembled fibers, [22] increased stability towards enzymatic degradation, [23] and access to new morphologies. [24] Inspired by this work, the enantiomeric disaccharide (LL) was synthesized starting from l-glucose (Supporting Information). Upon solvent switch, LL forms the enantiomeric helical fibers (right handed), confirming the direct correlation between oligosaccharide chirality and fiber helicity (Figure 3 A; Figure S11).…”
Section: Resultsmentioning
confidence: 99%
“…XRD confirmed that both enantiomers, DD(s) and LL(s), have identical crystallinity, whereas the racemic mixture packs in a different manner (Figure 3 B), as previously observed for heterochiral peptides assemblies. [24] Alteration of the 1:1 ratio between DD and LL creates irregularity in the structure, likely composed of flat structures and helical fibers ( Figure S13). AFM analysis of the flat aggregates (DD-LL(s)) suggests that the two enantiomers may construct a layer-by-layer supramolecular assembly (Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supramolecular hydrogels based on peptide self-assembly as potential nanocarriers have shown important applications in drug delivery, tissue engineering, cancer treatment and analysis (Wang et al, 2016a , 2018 , 2020a ; Yang et al, 2017 , 2020 ; Shigemitsu et al, 2018 ; Ren et al, 2019 ; Shang et al, 2019b ). Peptide monomolecules can self-assemble into specific nanostructures by non-covalent bonds including hydrophobic interaction, aromatic-aromatic stacking, hydrogen bond, etc., endowing them with ease of design, good biocompatibility and adjustable functions (Du et al, 2015 ; Chen et al, 2018 ; Shang et al, 2019a ; Yuan et al, 2019 ; Bera et al, 2020 ). In recent years, self-assembled peptides have been reported to exhibit immune-stimulating effects such as self-adjuvants.…”
Section: Introductionmentioning
confidence: 99%